Water level control system/ Zamshol Kamal Harun - Harun, Zamshol Kamal (1998)
Industrial automation is the key to the productivity and to improve quality in industry. In order to co-ordinate large components in the process control system, interactive manufacturing process, computer control is often needed. The availability of low cost computational power (in the form of microprocessor) has created a wide variety of applications for that power. In this thesis, the main objective is to make the pilot plant to be fully controlled by computer through the I/O Interfacing Card. Water level is the process variable. The system is designed for liquids (particularly water) at atmospheric pressure in non-hazardous area and can be applied for industrial process and home used. The overall system gives a closer look and understanding about the real process plant using direct digital control scheme